Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/psyg.12666
|View full text |Cite
|
Sign up to set email alerts
|

Current view on post‐stroke dementia

Abstract: Dementia is one of the leading complications after stroke affecting about one third of survivors. Prevalence of post‐stroke dementia (PSD) differs between studies due to variability in methodology, characteristics of included patients, type of stroke, diagnostic tools used to identify patients with dementia, or time when the assessment was performed. Patients diagnosed with PSD are at higher risk of mortality, disability, and institutionalization. Aetiology of PSD may include mixed overlapping processes such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 113 publications
(213 reference statements)
0
13
0
Order By: Relevance
“…Interactions between cognitive and motor impairment attract more attention during the last years. Prevalence of post-stroke CI is high and varies from 19 to 92 %, depending on severity and the method used for its detection [2,3,24]. Upper extremity motor impairment is a leading factor that impacts long-term disability due to a major role of manual dexterity in patients' self-care and functional independence.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between cognitive and motor impairment attract more attention during the last years. Prevalence of post-stroke CI is high and varies from 19 to 92 %, depending on severity and the method used for its detection [2,3,24]. Upper extremity motor impairment is a leading factor that impacts long-term disability due to a major role of manual dexterity in patients' self-care and functional independence.…”
Section: Discussionmentioning
confidence: 99%
“…The general characteristics of various treatments for post-stroke complications are shown in Table 1. Thus far, there are no specific FDA approved pharmacological treatments for PSCID [16]. Several agents have been proved to be effective for vascular dementia, such as cholinesterase inhibitors (galantamine, donepezil, or rivastigmine), memantine and gingko biloba [135].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…By definition, PSCI refers to all severities of cognitive impairment after stroke [6,7]. According to the results of previous studies, PSCI is common in patients with AIS, with the reported incidence of 30-50 % [8,9]. Clinically, patients with PSCI have poor quality of life [10].…”
Section: Introductionmentioning
confidence: 99%